Pengaruh Latihan Target dan Circuit Training terhadap Peningkatan Keterampilan Shooting Pemain Futsal - Ridho Aditya Pratama; Andri Arif Kustiawan; Agus Pribadi; Bimo Alexander (MAN Insan Cendekia Jambi, 2026)
This study was conducted to evaluate the impact of target practice and circuit training on enhancing the shooting skills of male extracurricular futsal players at SMK Negeri 9 Surakarta. Utilizing an experimental approach, the research adopted a two-group pretest-posttest design. A sample of 24 extracurricular participants was selected and distributed into two distinct intervention categories: the target practice group and the circuit training group. To measure the players' shooting proficiency, the TKDO Futsal shooting test was employed as the primary research instrument. Furthermore, the collected data were statistically analyzed through normality tests, homogeneity tests, paired sample t-tests, and independent sample t-tests. Based on the findings, target practice led to a notable enhancement in shooting proficiency, evidenced by a t-value of -19.621 and a significance value of 0.000 < 0.05. Similarly, the circuit training method demonstrated a significant positive effect on shooting skills, yielding a t-value of -13.619 with a significance level of 0.000 < 0.05. In terms of improvement rate, the target practice group achieved an increase of 18.42% , whereas the circuit training cohort recorded a higher advancement of 22.27%. Consequently, these data indicate that circuit training exerts a more substantial impact than target practice on developing the shooting capabilities of male extracurricular futsal players at SMK Negeri 9 Surakarta.